A New Species of the Genus Anatemnus (Pseudoscorpiones, Atemnidae) from China. (5th March 2012) - Hu, Jun-Fang; Zhang, Feng
Abstract : One new species belonging to Anatemnus Beier is reported from China under the name A. chaozhouensis sp. nov.